Reproduction of movement range and pressure force of the upper limbs in table tennis players - Bańkosz, Ziemowit (Akademia Wychowania Fizycznego w Poznaniu)
Introduction: Kinesthetic differentiation is frequently reflected in table tennis skills such as making an appropriate racket angle, adjustment of force and speed of arm movement upon hitting the ball, quick assessment of the arm position in reference to the ball, and making decisions about appropriate adjustments or changes. The level of kinesthetic differentiation of table tennis players should be fairly high. Aim of Study: The aim of this research was to assess and compare the accuracy of hand pressure force and range of supination – pronation reproduction in female table tennis players representing different sports levels, and in girls who did not practice table tennis. Material and Methods: The research was conducted on 32 female subjects: a group of table tennis players (n = 20) and a control group (n = 12). The subjects took part in six tasks aiming to demonstrate their levels of kinesthetic differentiation. Four of the tests enabled the assessment of accuracy of recreating pronation and supination of the forearm at the elbow joint. Two other tasks evaluated the force components and assessed the precision of recreating hand pressure force. Results: The precision indices for pronation performed with the dominant limb attained by the table tennis players were the lowest (i.e. the best) for those representing the highest sport level. The results of tasks designed to evaluate the ability of kinesthetic differentiation were slightly better for the table tennis players than for the control group. Conclusions: A statistically significant difference was observed only in supination of the dominant limb. This task may be specific to table tennis since the greater precision in the range of the dominant limb results from the use of the dominant arm in the game. The best results in supination of the dominant limb were obtained by the most advanced group of players with the longest training experience, which may indicate a correlation between kinesthetic differentiation and sports level in table tennis
Keywords: proprioception; kinesthetic differentiation; joint position sense; force sense; table tennis